Business models for the social mobile cloud : transform your business using social media, mobile Internet, and cloud computing - Shelton, Ted, 1966- (John Wiley & Sons, 2013)
"The combined impact of social technologies, the mobile Internet, and cloud computing are creating incredible new business opportunities. They are also destroying unprepared companies, transforming industries, and leaving behind workers who are unwilling or unable to adapt. Business Models for the Social Mobile Cloud reveals a compelling view from PwC of how the social mobile cloud and a combination of new technology changes are key players in a digital transformation in business and society that is moving more quickly and cutting more deeply than any technology transformation ever seen"--Provided by publisher.